Optimizing Fermentation Medium to Produce Cyclosporin a Using Response Surface Methodology - Sunaryanto, Rofiq (UI Scholars Hub, 2012)
Response surface methodology (RSM) is a three factorial model which illustrates the relationship between one or more independent variables. RSM can be used to optimize the fermentation medium for the production of Cyclosporin A from the isolate Tolypocladium inflatum. The optimal point of the response surface area is predicted by using a seconddegree polynomial model and applying the statistic model obtained from the central composite design (CCD). The results of optimizing the fermentation medium for Cyclopsorin using the three independent variables of glucose, casein, and KH2PO4 show that all three of the independent variables affect the production of Cyclosporin A. There is a positive interaction between the independent variables of glucose and casein, however, there is no visible interaction between glucose with KH2PO4 and casein with KH2PO4. By using the mathematical model the total optimum result obtained is 1230.5 mg L-1, glucose concentrate 28.5 g L-1, KH2PO4 concentrate 0.74 gL-1, and casein concentrate 9.8 g L-1. Laboratory validation shows that Cyclosporin A productivity is 1197.285 mg L-1. There is a value difference of 2.7% between the expected productivity of Cyclosporin A using the mathematical model and the actual production in laboratory tests.